"How do you shelter in place on the road?": Building Information Resilience through Communal Support for Van Dwellers in the Onset of Covid‐19. Issue 1 (14th October 2022) - Montague, Kaitlin
ABSTRACT: During the onset of the Covid‐19 pandemic, new health information was being disseminated at unprecedented rates which included ever‐changing mandates and regulations, resulting in information overload for many. Shelter in place orders are the pandemic‐related information that will be discussed. As these dynamic orders were announced and enforced, mobile populations—people who live in their vans or "van dwellers"—abandoned life on the road and rushed to loved ones to abide by social distancing directives. Others had nowhere to turn. This pilot study of van dweller's information practices focuses on the early weeks of the pandemic and how this population adapted to an overwhelming information environment. Using the information resilience conceptual framework, I describe how van dwellers adapted when a myriad of information and misinformation was circulating. The van dweller community, and their supporters, banded together to provide resources and safe spaces in a time of crisis.